Management of the cephalically malpositioned lower lateral crus in aesthetic rhinoplasty - Kovacevic, Milos; Riedel, Frank; Bran, Gregor M. (Facial plastic surgery, 2017)
Cephalic malposition of the lower lateral cartilages (LLC) gained increasing awareness as a distinct anatomical entity within the last years. It has become clear that this type of deformity is not amenable to traditional rhinoplasty techniques. Repositioning of the lateral crus of the LLC enables the surgeon to achieve significant and reliable changes in the shape and function of the nose. The authors present their technique for repositioning of the cephalically malpositioned LLC. Their method is based on a turn-in flap that is positioned along the caudal margin of the repositioned LLC. This flap straightens a convex LLC and gives reliable structural support to the caudal alar margin. In this article, they discuss the various indications of this technique, introduce a new, more precise concept for evaluation of the axis of the lateral crus of the LLC, and highlight additional details of this reliable technique.